2022
DOI: 10.3389/fimmu.2022.921947
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From Hyperammonemic Rats Induce Neuroinflammation in Cerebellum of Normal Rats: Role of Increased TNFα Content

Abstract: Hyperammonemia plays a main role in the neurological impairment in cirrhotic patients with hepatic encephalopathy. Rats with chronic hyperammonemia reproduce the motor incoordination of patients with minimal hepatic encephalopathy, which is due to enhanced GABAergic neurotransmission in cerebellum as a consequence of neuroinflammation. Extracellular vesicles (EVs) could play a key role in the transmission of peripheral alterations to the brain to induce neuroinflammation and neurological impairment in hyperamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Slices were transferred to incubation wells in a perfusion system (Campden Instruments, Model 7450) and incubated for 15 min at 35.5 °C in Krebs buffer for stabilization. Once stabilized, the slices from hyperammonemic rats were incubated during 30 min at 35.5 °C with the following treatments, all of them dissolved in Krebs buffer and aerated: 1 ng/mL of recombinant TGFβ (Miltenyi Biotec) (HA + rec TGFβ) [ 62 ], 1.2 µg/mL of anti-TGFβ antibody (Abcam) (HA + T), 10 µg/mL of extracellular vesicles from MSCs (HA + EVs) [ 43 ], 10 µg/mL of extracellular vesicles from MSCs previously treated with 1.2 µg/mL of anti-TGFβ antibody (Abcam) for 1 h at 37 °C (HA + EVs + anti-TGFβ) [ 83 ], 10 µg/mL of extracellular vesicles from MSCs lacking TGFβ as described above (HA + EVs lacking TGFβ; 10 µg/mL of extracellular vesicles from MSCs plus 2 µg/mL of galunisertib, an antagonist of TGFβ receptor (HA + EVs + anti-TGFβR [ 10 , 56 ]. All treatments were for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Slices were transferred to incubation wells in a perfusion system (Campden Instruments, Model 7450) and incubated for 15 min at 35.5 °C in Krebs buffer for stabilization. Once stabilized, the slices from hyperammonemic rats were incubated during 30 min at 35.5 °C with the following treatments, all of them dissolved in Krebs buffer and aerated: 1 ng/mL of recombinant TGFβ (Miltenyi Biotec) (HA + rec TGFβ) [ 62 ], 1.2 µg/mL of anti-TGFβ antibody (Abcam) (HA + T), 10 µg/mL of extracellular vesicles from MSCs (HA + EVs) [ 43 ], 10 µg/mL of extracellular vesicles from MSCs previously treated with 1.2 µg/mL of anti-TGFβ antibody (Abcam) for 1 h at 37 °C (HA + EVs + anti-TGFβ) [ 83 ], 10 µg/mL of extracellular vesicles from MSCs lacking TGFβ as described above (HA + EVs lacking TGFβ; 10 µg/mL of extracellular vesicles from MSCs plus 2 µg/mL of galunisertib, an antagonist of TGFβ receptor (HA + EVs + anti-TGFβR [ 10 , 56 ]. All treatments were for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, extracellular vesicles (EVs) have been suggested as an alternative mechanism for communication between the periphery and the brain in HE [2,[11][12][13] . The main reasons to study the contribution of EVs in the induction of neuroinflammation and the subsequent cognitive and motor impairment in HE are their ability to trespass the blood-brain-barrier (BBB) and the results reported in previous studies pointing out their relevance as intercellular mediators in different pathologies associated with chronic inflammation, including neurological diseases.…”
Section: Extracellular Vesicles As Novel Mediators Between the Periph...mentioning
confidence: 99%
“…Izquierdo-Altarejos et al demonstrated for the first time that intravenously injected HA-EVs reached the cerebellum of control rats, co-localizing with Purkinje neurons and microglia [11] . HA-EVs induced neuroinflammation in cerebellum, with microglia and astrocyte activation, and lead to motor incoordination in control rats.…”
Section: Evidence Of the Contribution Of Evs To Motor And Cognitive I...mentioning
confidence: 99%
“…Plasma EVs in hyperammonemic rats were changed and the TNF-α level was elevated. When injected into normal rats, EVs from plasma of hyperammonemic rats reached the cerebellum and caused changes in Purkinje neurons and microglia in particular particularly Purkinje neurons and microglia, further resulting in neuroinflammation and motor incoordination (Izquierdo-Altarejos et al 2022 ). Also, elevated TNF-α levels in EVs from hyperammonemic rats' blood activate the TNF receptor 1 (TNFR1)/C–C motif chemokine ligand 2 (CCL2)/BDNF/tropomyosin receptor kinase B (TrkB)/KCC2 and TNFR1/NF-kB/glutaminase/GABA transporter 3 (GAT3) pathways, thereby enhancing cerebellar GABAergic neurotransmission.…”
Section: Evs In Brain–liver Crosstalkmentioning
confidence: 99%
“…Also, elevated TNF-α levels in EVs from hyperammonemic rats' blood activate the TNF receptor 1 (TNFR1)/C–C motif chemokine ligand 2 (CCL2)/BDNF/tropomyosin receptor kinase B (TrkB)/KCC2 and TNFR1/NF-kB/glutaminase/GABA transporter 3 (GAT3) pathways, thereby enhancing cerebellar GABAergic neurotransmission. As a result, microglia activation, increased GABAergic neurotransmission, and motor incoordination occur (Izquierdo-Altarejos et al 2022 ). Apolipoprotein E4 (ApoE4) alleles are strongly associated with age-related cognitive impairment and AD (Kanekiyo et al 2014 ; Strittmatter et al 1993 ).…”
Section: Evs In Brain–liver Crosstalkmentioning
confidence: 99%